Design and aerodynamic analysis of the morphing waverider with rotating telescopic wing for wide-speed-range flight - Qiao, Nanxuan; Ma, Tielin; Jing, Biao; Fu, Jingcheng; Zhang, Ligang (Aerospace science and technology, 2025)
•A novel morphing waverider with rotating telescopic wings is proposed for wide-speed-range flight.•The vehicle's configuration supports clustered launch deployment and runway landing capabilities.•Multi-objective optimization achieves a balance between volumetric efficiency, L/D ratio, and wing area.•A rear fairing design significantly improves aerodynamic performance in subsonic regime.•The fuselage contributes 49.5 % of total lift at high angles of attack, enhancing stall resistance. Wide-speed-range vehicles represent a burgeoning research area in aerospace, challenged by the conflicting aerodynamic demands of different flight regimes. This study proposes a novel "waverider with rotating telescopic wing" configuration for clustered launch deployments, capable of morphing to meet both hypersonic and subsonic flight requirements. The research focuses on two key aspects: firstly, presenting a morphing vehicle design for wide-speed-range flight; and secondly, developing a multi-objective optimization method for the waverider fuselage subject to multiple constraints, followed by a detailed analysis of the design results. Performance analysis under various flight conditions revealed that rear surface drag significantly hinders subsonic performance. To address this, the study investigates the design and impact of a rear fairing across different speeds. Results demonstrate that the rear fairing effectively enhances aerodynamic performance in both hypersonic and subsonic regimes. This promising configuration addresses the challenges of wide-speed-range flight while enabling cost-effective clustered launches. When coupled with reusable launch vehicles, it unlocks significant potential for applications such as rapid intercontinental transportation.